Partial normalisation of cardiac mechanics with active CRT in patients with chronic failure: a novel application of 3.0T CMR. (25th November 2020) - Koshy, A; Gierula, J; Paton, M; Swoboda, P; Toms, A.G; Saunderson, C; Shelley, D; Broadbent, D; Plein, S; Kearney, M.T; Witte, K.K
Abstract: Introduction: Cardiac resynchronisation therapy (CRT) is a routine treatment for chronic heart failure (CHF) with reduced ejection fraction and conduction delay to improve prognosis. Cardiac mechanics in patients with CHF are believed to be altered from controls based on invasive and echocardiographic based data. Technological advancements in cardiac magnetic resonance (CMR) and devices enable investigation of the cardiac response to CRT over a range of heart rates. Methods: Patients with a CRT-D device were enrolled from heart failure clinics at Leeds General Infirmary, UK. After a MRI safety assessment, a baseline device check was conducted by a cardiac physiologist. Left ventricular (LV) volumes and systolic BP were measured at baseline and heart rates of 75, 90, 100, 115, 125, and 140 (randomised order) with CRT active and intrinsic conduction. All scans were conducted using a 3.0 T Siemens Prisma MRI scanner. Analysis of the scans used commercially available software. LV contractility was derived as a ratio of the LV end systolic volume and systolic BP. A post scan device interrogation was conducted to assess for scanning safety. Control participants with a 3.0T MR-conditional dual chamber pacemakers completed a similar protocol. Results: Scanning was conducted in 17 CRT patients and 13 controls with a pre and post device and lead interrogation. No patient experienced symptoms related to scanning or device failure. The mean LV ejection fraction at baseline in the CRT cohort was 33.7±12.9%. Left ventricular ejection fraction fell across both cohorts as paced heart rate increased with reduced deterioration in control patients and those with CRT active. Peak LV cardiac output was significantly higher during active CRT (p<0.05). LV contractility was relatively static with CRT disabled (r2=0.13, p=0.38) and improved with CRT active (r2=0.91, p=0.01) and in controls (r2=0.74, p=0.01). Peak LV strain occurred at 100bpm during active CRT and in control patients whereas CRT disabled resulted in earlier deterioration. Conclusion: We have demonstrated improvements in cardiac output and contractility consequent to active CRT using 3.0T CMR and subsequently validated via strain analysis. CRT appears to partially normalise cardiac mechanics across the range of heart rates studied. Further work is required to explore this phenomenon on a cellular or metabolic level. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): AK is supported by an unconditional grant provided by Medtronic